Eulerian CFD modelling for biomass combustion. Transient simulation of an underfeed pellet boiler. (1st September 2015) - Gómez, M.A.; Porteiro, J.; Patiño, D.; Míguez, J.L.
Highlights: A 3D transient model for the simulation of fixed bed combustion was applied in a biomass boiler. The thermal conversion of solid wood was modelled by a group of transport equations. An advective motion model was introduced to account for the bed movements caused by the feeding process. The models were applied to the geometry of real boiler to analyse their overall behaviour. Abstract: This paper describes a transient model for biomass combustion in a fixed bed boiler. This method implements several submodels which address a variety of conversion processes and interactions between solid and gas phases. A set of Eulerian variables will be defined representing the solid phase state as well as the governing equation model for both the evolution and the thermal conversion of the bed. The solid phase components including the ash content is divided into solid and volatile elements. The fuel feeding is modelled by an advective flux term in the transport equations of the solid phase variables. The advective flux term includes a treatment that prevents the numerical diffusion beyond the bed's surface. This method also includes heat and mass transfer models between phases, particle and bed shrinkage, porous media and gas reactions. Several experimental tests have been simulated to contrast model behaviour. The primary variable profiles of the solid phase in the bed and gas phase in the furnace have been analysed. The results show reasonably good predictions for the exchanged heat and the flue gas concentrations.